UMA INVESTIGAÇÃO EM CORPUS PARALELO SOBRE EXPRESSÕES FIXAS E MARCADOR DE REFORMULAÇÃO EM LAÇOS DE FAMÍLIA, A VIA CRUCIS DO CORPO E ONDE ESTIVESTES DE NOITE, DE CLARICE LISPECTOR E AS RESPECTIVAS TRADUÇÕES FAMILY TIES E SOULSTORM - Bonalumi, Emiliana Fernandes (2010)
By means of the application of Wordsmith Tools, we observed higher frequencies of two fixed expressions: from time to time and in the middle of , and a reformulation marker: that is, which allowed us to identify in the target texts some tendencies of the translators Giovanni Pontiero and Alexis Levitin.